Low Initial Adherence with Flash Glucose Monitoring is Not a Predictor of Long-Term Glycemic Outcomes: Longitudinal Analysis of the Association Between Experience, Adherence, and Glucose Control for FreeStyle Libre Users - Šoupal, Jan; Kao, Kalvin; Brandner, Laura; Grunberger, George; Prázný, Martin (Diabetes therapy, 2023)
INTRODUCTION: Frequent scanning of FreeStyle Libre (FSL) flash glucose monitoring sensors is known to be important whilst wearing an active sensor, but adherence to sensor reapplication is also critical to effective glucose monitoring. We report novel measures of adherence for users of the FSL system and their association with improvements in metrics of glucose control. METHODS: Anonymous data were extracted for 1600 FSL users in the Czech Republic with ≥ 36 completed sensors from October 22, 2018 to December 31, 2021. "Experience" was defined by the number of sensors used (1-36 sensors). "Adherence" was defined by time between the end of one sensor and the start of the next (gap time). User adherence was analyzed for four experience levels after initiating FLASH; Start (sensors 1-3); Early (sensors 4-6); Middle (sensors 19-21); End (sensors 34-36). Users were split into two adherence levels based on mean gap time during Start period, "low" (> 24 h, n = 723) and "high" (≤ 8 h, n = 877). RESULTS: Low-adherence users reduced their sensor gap times significantly: 38.5% applied a new sensor within 24 h during sensors 4-6, rising to 65.0% by sensors 34-36 (p < 0.001). Improved adherence was associated with increased %TIR (time in range; mean + 2.4%; p < 0.001), reduced %TAR (time above range; mean - 3.1%; p < 0.001), and reduced glucose coefficient of variation (CV; mean - 1.7%; p < 0.001). CONCLUSIONS: With experience, FSL users became more adherent in sensor reapplication, with associated increases in %TIR, and reductions in %TAR and glucose variability.